Nucleotide changes in Vibrio parahaemolyticus plasmids isolated from affected shrimp by the acute Hepatopancreatic Necrosis Disease (AHPND) in Tumbes (Peru) - Delgado-Olivares, Leslie Giovanna (2026)
Although Acute Hepatopancreatic Necrosis Disease (AHPND) causes significant shrimp mortality worldwide, lower mortality rates have been reported in South America. This study analyzed the nucleotide sequences of three plasmids from Vibrio parahaemolyticus strains isolated from infected shrimp in Tumbes, Peru; all sequences are deposited in the GenBank database. The bioinformatic analysis revealed high similarity to the pVA1 plasmid, with complete sequence homology in the genes encoding the PirAB binary toxin in two of the plasmids and a partial deletion in the pirAVP gene in the third. Additionally, all three plasmids harbored mutations in other genes, likely associated with the disease.